Leveraging Internet of Things (IoT) for Enhanced English Language Learning: Opportunities and Challenges in Modern Classrooms - Fakhrurriana, Ria; Herdina, Griselda Gian Heris (Proceeding International Conference on Religion, Science and Education, 2025)
The technological revolution in various sectors continues to change including in the education sector. The Internet of Things (IoT) holds new opportunities for English language students in the digital era by offering a variety of personalised and integrated interactive experiences. This conceptual article discusses how IoT can be integrated with English language learning classrooms in an effort to improve teaching and learning effectiveness starting from a basic understanding of IoT and its potential in education. The article will discuss various IoT applications such as smart devices, automated assessment systems, and adaptive learning platforms that create efficient learning. In addition, this article also focuses to discuss the challenges faced in implementing IoT in the educational environment. This conceptual article explores how IoT can be effectively integrated into English language classrooms to boost teaching and learning efficiency.